EVALUASI KESESUAIAN DI AREAL PENGGUNAAN LAIN UNTUK TANAMAN GAMBIR (Uncaria gambier Roxb.) DI KECAMATAN SALAK, KABUPATEN PAK-PAK BHARAT - Fitra Syawal Harahap; Abdul Rauf; Deni Elfiati; Sarifuddin Sarifuddin; Simon Haholongan Sidabukke (Jurnal Tanah dan Sumberdaya Lahan, 2020)
Salak Sub-district has a land area use covering an area of 3607.20 ha or 13.67% of the total area of 25640.99 ha Pakpak Bharat so that other land area use (APL) in Salak Sub-district needs to be supported with information on land suitability so that the potential of very large land can be utilized in agricultural cultivation activities, with the expectation that productivity can improve the welfare of local people who mostly work as farmers. The purpose of this research is to know and evaluate the characteristics of the actual land suitability level and the suitability of potential land in Salak Subdistrict so that it is known that suitable land conditions for agricultural commodities will be developed to increase crop Gambir (Uncaria gambirÂ  Roxb.) productivity. The research method used survey method. Unit of land based on soil maps, maps of slope, elevation maps, land cover maps, and consists of 8 units of land and 18 sampling points. Research data were analyzed using matching method. Research results Limiting factor and improvement effort of plant commodity of Gambir Plant (Uncaria gambir Roxb.) Rooting factor (rc) and nutrient retention (nr). Improvement efforts that can be done by making drainage and calcification CaCO3,